Image visualization encryption algorithm based on Shamir threshold secret key sharing - Yifu TAN,Zichen LI (网络与信息安全学报, 2018)
An image visualization encryption algorithm with authentication function by using Shamir scheme was proposed.The main idea of this algorithm is to obtain the data by segmenting the binary secret image into blocks.Then,Shamir scheme was used to obtain the sub-secret data and simultaneously sign the secret image with the SM2 signature algorithm.And it would embed the shared data and signature information into carrier images.When the restoration is required,a specified number of sub-secret images are required for information extraction,restoration and authentication.The simulation experiment of the scheme shows that the secret image sharing scheme improves the security of secret image storage and transmission.